KARAKTERISASI LUCUTAN PLASMA YANG DIBANGKITAN DENGAN ELEKTRODA AKTIF MENGGUNAKAN JARUM SUNTIK DAN ELEKTRODA PASIF BERUPA BIDANG LENGKUNG PADA KONDISI ATMOSFIR - Ardhianto, Khamdi Bagas; Bawono, Ari; Muhlisin, Zaenul (BERKALA FISIKA, 2020)
Research on characterization of plasma discharge generated by active electrodes using syringes and passive electrodes in the form of curved fields under atmospheric conditions has been carried out. The study was conducted to obtain the characteristics of the I-V relationship and visual picture of the formed discharge. The syringe used was 0.6 mm in diameter and was used as an active electrode. Plasma discharge was generated by connecting the syringe and curvature with a high-voltage DC (HV DC) generator. The syringe was connected with a positive pole, given a potential difference gradually to the maximum of HV DC and observed for the plasma discharge. After that, the syringe was connected to the negative pole, then given a potential difference gradually until the maximum of HV DC and observed plasma discharge. The distances between the point electrode and the curve electrode were 2 mm, 3 mm, 4 mm and 5 mm. The results showed that the relationship between current and voltage on the syringe as positive and negative electrodes followed the equation I ~ V2 until just before the spark discharge appeared and then arc discharge. The variation in the distance between the electrodes in each syringe treatment affected the amount of voltage needed to generate discharge. The greater the distance between the electrodes, the greater the voltage needed to reach the arc discharge.